Pneumatic System of Variable-Force Corn Threshing - A. G. Pastukhov; D. N. Bakharev; S. F. Volvak; R. V. Chernikov (Сельскохозяйственные машины и технологии, 2019)
Differentiation of the force applied to the cobs of seed corn in the process of threshing allows minimizing the amount of macro- and micro-damage to the grain, which maintains the potential yield level of this crop. (Research purpose) To develop an automatic control system for active pneumatic elements of the deck of the threshing-and-separating unit capable of varying the pressing force of the spikes applied to the cobs of seed corn in different parts of the threshing chamber to minimize the crop damage. (Materials and methods) The authors have used the methods of system analysis, designing the operating algorithms of automated mechanical systems, electronics and general electrical engineering. (Results and discussions) The authors offer an advanced design of the threshing-and-separating unit for seed corn. The design features an active pneumatic deck with an automatic control system varying the pressing force of separate deck spikes to the cob grain directly in the course of threshing. For air inflating and lowering, two valves are installed in each of the 16 airbags, 32 control relays being used. The operation process is automatized through the Atmega 2560 controller regulating the amount of pressure in the airbags forcing the spikes against the grain in the process of threshing. The authors propose a schematic diagram describing the operation algorithm of the controller with pressure control units in deck airbags. By programming the controller, an operator can change the amount of pressure in the airbags, thus adjusting the force of direct and precise pressing the deck spikes to the corn cobs, for any airbag and in any part of the deck. (Conclusions) It has been determined that the destructive pressing force of 55 Newtons can be achieved in certain combinations of the membrane thickness, the pressure in the airbags and the pressing depth of the spikes. The proposed design of the threshing device with a system of automated pressure control in the deck airbags allows varying the force of threshing, which minimizes the amount of macro- and micro-damage to the seed corn grain and thus maintains the potential yield level of this crop.